2002
DOI: 10.1021/bi0258851
|View full text |Cite
|
Sign up to set email alerts
|

Photoexcitation of Tryptophan Groups Induces Reduction of Two Disulfide Bonds in Goat α-Lactalbumin

Abstract: Illumination of goat alpha-lactalbumin (GLA) with 280 or 295 nm light results in tryptophan-mediated photolysis of disulfide bonds within the protein. The photolysis is not dependent on the absence or presence of Ca(2+) and is observed as well on illumination of native and of partially unfolded GLA. However, photolysis of native GLA results in a partial unfolding of the protein. The latter phenomenon is most clearly observed on fluorescence measurements at low temperatures (near 3 degrees C). The photolysis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
150
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(165 citation statements)
references
References 25 publications
14
150
1
Order By: Relevance
“…It has been demonstrated that electron attachment to a disulfide bond leads to significant bond weakening and formation of stable radical species at low temperature in solution [31,32]. The reduction of disulfide bonds by photoexcitation of tryptophan groups in goat ␣-lactalbumin has been described before [33]. This process involves transfer of photo-electrons from a proximal tryptophan to the disulfide bond and subsequent cleavage into a thiolate ion and thiyl radical (see Supplemental Materials).…”
Section: Gas-phase Scrambling Of Disulfide Bonds In Sel24kmentioning
confidence: 99%
“…It has been demonstrated that electron attachment to a disulfide bond leads to significant bond weakening and formation of stable radical species at low temperature in solution [31,32]. The reduction of disulfide bonds by photoexcitation of tryptophan groups in goat ␣-lactalbumin has been described before [33]. This process involves transfer of photo-electrons from a proximal tryptophan to the disulfide bond and subsequent cleavage into a thiolate ion and thiyl radical (see Supplemental Materials).…”
Section: Gas-phase Scrambling Of Disulfide Bonds In Sel24kmentioning
confidence: 99%
“…1 An important feature of tryptophan photolysis is the potential for photoinduced electron transfer to nearby disulfide bridges 1 where disulfide reduction leads to a thiolate and a thiyl radical. 1 Thiyl radicals can form also via direct light-induced homolysis of cystine disulfide bonds [29][30][31][32] and a number of reaction products have been characterized for thiyl radical pairs generated in such way 1, [33][34][35][36][37] For completeness, we note that disulfide bonds can also cleave via C-S bond breakage into carbon-centered radicals and perthiyl radicals, but this process appears to prevail for β-alkyl substituted disulfides such as, for example, penicillamine. 30 For comparison, the light-induced cleavage of glutathione disulfide led predominantly to thiyl radicals.…”
Section: Chemistry Of Photooxidationmentioning
confidence: 99%
“…[32] From a mechanistic point of view, it can be speculated that tryptophan residues present in BSA were responsible for the observed hyperglycosylation. It has been reported that prolonged near-UV irradiation of goat a-lactalbumin [33] or hen egg white lysozyme [34] induces tryptophan residue excitation and this is followed by electron transfer to some nearby cystine S À S bonds with consequential cleavage into thiol radical and thiolate anion. The same mechanism may be operative in the BSA irradiation, thus providing an extra number of thiol radicals centered on the former cystine residues.…”
mentioning
confidence: 99%